Caracterización y análisis físico-químico de la microcuenca quebrada la adobera del municipio de Zipacón (2022)
The main objective of this work is to identify the physical and chemical characteristics of the Quebrada La Adobera micro-watershed in the municipality of Zipacón (Cundinamarca), for which sampling was carried out at three points of the micro-watershed: upper, middle and? lower part in order to perform an analysis of physicochemical parameters to determine the water quality such as: hydrogen potential (PH), total dissolved solids (TDS), dissolved, oxygen concentration (DO), turbidity, oxidation-reduction potential (ORP), electrical conductivity (E. C), temperature and salinity. It should be noted that in addition to the physicochemical parameters, analyses of the organoleptic properties present in the water, specifically, color and microbiological analyses such as total coliforms and fecal coliforms (E.coli) were also carried out. The samples from each of the points were collected in situ and analyzed in the environmental engineering laboratory of the Antonio Nariño University